Health law and policy, devolution and Brexit. Issue 9 (2nd September 2021) - McHale, Jean; Speakman, Elizabeth M.; Hervey, Tamara; Flear, Mark
ABSTRACT: The National Health Service (NHS) was a critical symbolic issue in the European Union (EU) referendum. The practical ramifications of Brexit on UK patients, professionals, health research and public health are significant, with particular challenges in the devolved nations/jurisdictions. Whatever the form of Brexit, and future EU–UK relationship(s), these challenges will form a key part of health governance post-Brexit. A multilevel governance approach will help make sense of this new regulatory terrain, and its effects for health and the NHS. It is important to understand, raise awareness of and navigate the different Brexit effects for health in the devolved nations/jurisdictions, and the different Brexit effects for different aspects of health and its governance; the broader economic, social and cultural contexts of Brexit and their indirect implications for health; and how legal responsibilities for healthcare are a poor fit with the emerging realities of managing Brexit.